2003
DOI: 10.1213/01.ane.0000081722.09164.d5
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Pain on Health-Related Quality of Life in the Immediate Postoperative Period

Abstract: Severity of postoperative pain may affect quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
0
5

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 166 publications
(84 citation statements)
references
References 17 publications
3
75
0
5
Order By: Relevance
“…It has been proposed that liposomal bupivacaine can improve the duration of effectiveness for PAI and thus may provide sufficient analgesia while also reducing the amount of opioid medications delivered for effective pain control. The current study occurred in settings that already had established total joint pathways in place, including preoperative education [70], patient-focused care initiatives [3,17,19,36,43,45,60,67,87], multimodal analgesia regimens [9,10,16,20,24,26,35,38,53,72,76,78,80,83], and postoperative rehabilitation pathways [16,51,77] to focus the results on the three randomized treatment groups described. We found that the primary outcome measure of pain control was better at 6 and 12 hours postoperatively in the liposomal bupivacaine PAI and spinal morphine groups compared with the ropivacaine PAI group.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that liposomal bupivacaine can improve the duration of effectiveness for PAI and thus may provide sufficient analgesia while also reducing the amount of opioid medications delivered for effective pain control. The current study occurred in settings that already had established total joint pathways in place, including preoperative education [70], patient-focused care initiatives [3,17,19,36,43,45,60,67,87], multimodal analgesia regimens [9,10,16,20,24,26,35,38,53,72,76,78,80,83], and postoperative rehabilitation pathways [16,51,77] to focus the results on the three randomized treatment groups described. We found that the primary outcome measure of pain control was better at 6 and 12 hours postoperatively in the liposomal bupivacaine PAI and spinal morphine groups compared with the ropivacaine PAI group.…”
Section: Discussionmentioning
confidence: 99%
“…This reduction in pain intensity may play a critical role in a patient's recovery process, and it has been shown in one study that pain severity postoperatively correlates with health-related quality of life. 22 Additionally, pain is one of the most common reasons for hospital readmissions. 23 All review studies but one 17 reported a decreased requirement for rescue analgesia among patients receiving femoral nerve blocks.…”
Section: Discussionmentioning
confidence: 99%
“…The favourably low incidence of nausea and vomiting was probably multifactorial. Associated factors might have included the dexamethasone-ondansetron combination in the control group, 25,26 use of ondansetron within the first six hours, 27 and improved analgesia and reduced opioid consumption 28 in Groups D1 and D2.…”
Section: (D1) Group 3 (D2) (N = 30) (N = 30) (N = 30) Vas (Rest) Vas mentioning
confidence: 99%